Identifikasi Kapabilitas Masyarakat Sebagai Dasar Pembangunan Desa Secara Endogen di Kecamatan Ampek Angkek Kabupaten Agam - Marlina Wirmas; Retno Widodo Dwi Pramono (Jurnal Pembangunan Nagari, 2021)
Exogenous rural development policy that tends to be centralized and sector-based has caused high dependency of villages to the central government program. Law on Villages then enacted to overcome those issues by shifting the paradigm into endogenous rural development through authorizing villages to self-manage the development. Capability approach is used to identify the actual state of community’s well -being, which reflects the freedom of doing and being of the people, so that it can be utilized as the basis for mapping the strength and issues. Assessment is conducted by measuring the level of availability and functioning of five categories of assets that represent modals and opportunities needed by the community to achieve their desired purpose. Research is conducted in Ampek Angkek District by distributing questionnaires to rate the indicators which consist of 51 assets from the five categories. The analysis finds that on average, asset availability index is 0,61 (adequate towards good quality); asset functioning is 1,23 (helpful) and overall community capability index is 0,144 represent fairly good condition, which available assets providing benefits and functions to community to perform its activities. Furthermore, the mapping of the assets of each village shows that there are several assets that need to be improved as input for the rural development agenda. Recommendations above those results are the need to increase the social capital’s community, and support assistance from related stakeholder to achieve more self managing and participatory rural development as basis for endogenous rural development.